Effect of Acorus calamus L. extract on growth performance and blood parameters of common carp (Cyprinus carpio L.) cultivated in a recirculation system - Katya Velichkova; Ivaylo Sirakov; Stefka Stoyanova; Georgi Zhelyazkov; Yordan Staykov; Todor Slavov (Journal of Central European Agriculture, 2019)
The aim of this study was to determine the effect of the sweet flag (A. calamus L.) extract addition of growth performance, haematological (white blood cells, red blood cells, hemoglobin, hematocrit) and biochemical (glucose, urea, creatinine, total protein, albumin, ASAT, ALAT, Ca, P, Mg, triglycerides, cholesterol) blood parameters of common carp (Cyprinus carpio L.) cultivated in recirculation system. Carps were randomly selected and distributed into four concrete tanks for the growth trial (8 fish/tank). Fish were divided into experimental (E) and control groups (C), each of them with two replicates and mean initial weight 908.5±171.2 g and 913.8±147.4 g, respectively. They were fed with pelleted carp feed with 25% crude protein, produced by the "Top mix" company, having a granule size of 6 mm. To the fish feed on the experimental group (E) was added 1% aqueous extract of A. calamus root, as well as oiling the pellets with 5 mL of sunflower oil for every 100 g of feed. Carps from control group (C) were fed with feed only greased with the same amount of sunflower oil. The daily ration that the studied fish received was 1.8% of their live weight. The duration of the trial period was 45 days. At the end of the experiment with 5.2% was measured a higher average live weight in the fish receiving the sweet flag supplement compare to the value of this parameter of carps from control group, and the differences were statistically significant (P<0.05). The survival rate was 100% in control and experimental variants. At the end of the experiment, the average individual weight gain of the experimental fish fed with the supplement was higher with 53.2% compared to this one of carps from control. The feed conversion ratio in experimental carps, supplemented with 1% sweet flag extract was with 16.1% lower than that of control fish, although the differences were not relevant (P>0.05). Better blood biochemical and haematological parameters were measured in carp fed with sweet flag supplement.